Carrier Screening and Prenatal Diagnosis for Spinal Muscular Atrophy in Ningde City, Fujian Province - JiaoJiao Lu; Xian Zheng; Jing Yang; WenXu Dong; LuoYuan Cao; Xiaomei Zeng; Qinjuan Wu; Xunyan Chen; XianGuo Fu (Molecular Genetics & Genomic Medicine)
ABSTRACT Objective This study aimed to screen for SMN1 (OMIM#600354) deletion carriers in 6035 pregnant women in the eastern part of Fujian Province, to provide a theoretical basis for genetic counseling and further prenatal diagnosis of the disease, and to explore the carrier frequency and clinical significance of spinal muscular atrophy (SMA) in the eastern part of Fujian Province. Methods Pregnant women treated at the prenatal diagnosis institution of Ningde Municipal Hospital of Ningde Normal University from February 2022 to October 2023 were selected as research subjects. The exons 7 and 8 (E7 and E8) of the survival of motor neuron 1 gene (SMN1) from 6035 pregnant women were detected using real‐time fluorescence quantitative PCR (qPCR). Spouses of pregnant women with positive results were recalled for gene detection, and prenatal diagnosis was performed for both partners as carriers. Results A total of 100 SMA carriers were detected in 6035 pregnant women, including 98 with heterozygous deletions of E7 and E8 of the SMN1 gene and two with heterozygous deletions of E7 only. The carrier frequency was 1.66%. One couple was both identified as SMA carriers, and their fetus with a homozygous deletion of E7 and E8 of the SMN1 gene was finally detected by prenatal diagnosis and gene analysis. Conclusion The frequency of SMA mutation in the Ningde area of Fujian province has been identified, which can provide the basis for genetic counseling and prenatal diagnosis. Interventional prenatal genetic diagnosis for high‐risk fetuses can effectively prevent the birth of children with SMA and is crucial for preventing and controlling birth defects.